Who will carry out the tests that would be necessary for proper safety evaluation of food emulsifiers? - Katalin F. Csáki; Éva Sebestyén (Food Science and Human Wellness)
Surfactant food emulsifiers are among the most extensively used food additives. Like all authorized food additives, emulsifiers have been evaluated by risk assessors, who consider them as safe. However, there are growing concerns among scientists about their possible harmful effects on intestinal barriers and microbiota. It is also suggested that emulsifier consumption might be one of the main causes of the rising incidence of a number of diseases, such as allergic diseases, celiac disease, type I diabetes and Crohn’s disease. Moreover, it has recently been suggested that emulsifier consumption might contribute to the development of metabolic syndrome and can promote colitis-associated colorectal cancer also. This paper provides an overview of the current scientific knowledge on possible effects of surfactant emulsifiers on intestinal barriers and also of regulatory risk assessment approaches. Our main objective is to reveal the reasons for the discrepancies between the opinions of risk assessors and the scientific world. We would like to draw the attention of the academic world to the need of specific in vivo and/or clinical studies for each emulsifier in order to help risk assessors make adequate evaluations and rule out with certainty that authorized food emulsifiers pose a safety concern to consumers’ health. Keywords: Food emulsifiers, Surfactants, Intestinal barriers, Crohn’s diseases, Microbiota, Risk assessment, EFSA